PENERAPAN PENDEKATAN STEAM DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN LITERASI SAINS SISWA KELAS IV SD ANAK SALEH MALANG - Khoiriya, Rika Mellyaning; Oktarianto, M Luthfi; Rohmiati, Dyah Palupi (JUSEDA, 2023)
Science education plays a crucial role in equipping students with essential knowledge about themselves and their environment. In the 21st-century educational era, emphasizing the development of critical thinking skills becomes essential, given the complex challenges faced by modern society. This study focuses on the application of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in science education to enhance the critical thinking abilities and scientific literacy of fourth-grade students at Anak Saleh Elementary School in Malang. Through a Classroom Action Research method conducted collaboratively with teachers, this research observes the effectiveness of the STEAM approach in creating a conducive learning environment for students to actively construct their knowledge through real activities. The research subjects included 28 students, comprising 11 boys and 17 girls. Data were collected through interviews, observations, and tests, both multiple-choice and descriptive, to produce qualitative and quantitative data. Initial results show a significant improvement in critical thinking and scientific literacy skills, with the percentage of students achieving the minimum mastery criteria (MMC) increasing from 71.42% in the first cycle to 89.28% in the second cycle. These findings affirm that the STEAM approach can be an effective strategy in enhancing students' critical thinking and scientific literacy skills while providing insights for the development of more innovative science education methods in the future.